Diversifying of Chemical Structure of Native Monascus Pigments - Liu, Lujie; Zhao, Jixing; Huang, Yaolin; Xin, Qiao; Wang, Zhilong (Frontiers in Microbiology, 2018)
Red Yeast Rice, produced by solid state fermentation of Monascus species on rice, is a traditional food additive and traditional Chinese medicine. With the introduction of modern microbiology and biotechnology to the traditional edible filamentous fungi Monascus species, it reveals that the production of red colorant by fermentation of Monascus species involves the biosynthesis of orange Monascus pigments and further chemical modification of orange Monascus pigments into the corresponding derivates with various amine residues. Further study indicates that non-Monascus species also produce Monascus pigments as well as Monascus-like pigments. Based on the chemical modification of orange Monascus pigments, the diversification of native Monascus pigments, including commercial food additives of Red Monascus Pigments® and Yellow Monascus Pigments® in Chinese market, was reviewed. Furthermore, Monascus pigments as well as their derivates as enzyme inhibitors for anti-obesity, hyperlipidemia, and hyperglycemia was also summarized.